Skin Ceramide Profile in Children With Atopic Dermatitis - Shen, Chun-Ping; Zhao, Mu-Tong; Jia, Zhi-Xin; Zhang, Jin-Lan; Jiao, Lei; Ma, Lin (Dermatitis, 2018)
Atopic dermatitis (AD) is a common disease, which involves a disruption of the skin barrier function. Skin ceramide (CER) composition, which plays crucial roles in maintaining the barrier function of the stratum corneum, is changed in patients with AD. The aim of this study was to identify and quantify skin CER subclasses in association with disease severity in pediatric patients with AD. Two hundred thirteen patients were entered into the observational study. We compared their CER profiles using normal-phase high-performance liquid chromatography coupled with dynamic multiple reaction monitoring mass spectrometry. In total, 12 subclasses of CERs were identified. We found that 2 subclasses, that is, CER[AS] and CER[NS], were elevated (P = 0.007 and 0.012, respectively) and correlated with Severity Scoring of Atopic Dermatitis (P = 0.004 and 0.004, respectively). Skin CER abundances are changed in children with AD compared with control subjects.